2019
DOI: 10.3847/1538-4365/aaee85
|View full text |Cite
|
Sign up to set email alerts
|

The Spitzer-HETDEX Exploratory Large Area Survey. II. The Dark Energy Camera and Spitzer/IRAC Multiwavelength Catalog

Abstract: We present the ugriz-band Dark Energy Camera (DECam) plus 3.6 and 4.5 µm IRAC catalogs for the Spitzer /HETDEX Exploratory Large-Area (SHELA) survey. SHELA covers ∼ 24 deg 2 of the Sloan Digital Sky Survey (SDSS) "Stripe 82" region, with seven bandpasses spanning a wavelength range of 0.35 to 4.5 µm. SHELA falls within the footprint of the Hobby-Eberly Telescope Dark Energy Experiment (HETDEX), which will provide spectroscopic redshifts for ∼ 200,000 Lyα emitters at 1.9 < z < 3.5 and also for ∼ 200,000 [OII] e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 16 publications
3
68
0
Order By: Relevance
“…In the local Universe, recent integral field spectroscopy (IFS) studies (e.g., Sánchez et al 2012, Ma et al 2014, Bundy et al 2015 have confirmed that the most massive galaxies in the nearby Universe have old stellar populations indicative of early growth and rapid quenching at early times (e.g., Pérez et al 2013, Greene et al 2015. Deep, wide-area surveys (e.g., Jannuzi & Dey 1999, de Jong et al 2015, Papovich et al 2016, Wold et al 2019) are necessary to compile large, statistically significant samples of rare systems, such as massive galaxies, overcome cosmic variance, and probe a wide range of environments. As massive galaxies present a challenge to the overall hierarchical structure formation expected in ΛCDM cosmology (e.g., Cowie et al 1996, Fontanot et al 2009), it is imperative that statistically significant samples of massive galaxies are constructed.…”
Section: Introductionmentioning
confidence: 99%
“…In the local Universe, recent integral field spectroscopy (IFS) studies (e.g., Sánchez et al 2012, Ma et al 2014, Bundy et al 2015 have confirmed that the most massive galaxies in the nearby Universe have old stellar populations indicative of early growth and rapid quenching at early times (e.g., Pérez et al 2013, Greene et al 2015. Deep, wide-area surveys (e.g., Jannuzi & Dey 1999, de Jong et al 2015, Papovich et al 2016, Wold et al 2019) are necessary to compile large, statistically significant samples of rare systems, such as massive galaxies, overcome cosmic variance, and probe a wide range of environments. As massive galaxies present a challenge to the overall hierarchical structure formation expected in ΛCDM cosmology (e.g., Cowie et al 1996, Fontanot et al 2009), it is imperative that statistically significant samples of massive galaxies are constructed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the NEWFIRM K-band data, the SHELA survey includes ugriz imaging from the Dark Energy Cam-era over 17.5 deg 2 (DECam; Wold et al (2019)) and deep 3.6 and 4.5 µm imaging from Spitzer/IRAC (Papovich et al 2016). The riz−band selected DECam catalogs reach a 5σ depth of ∼ 24.5 AB mag.…”
Section: Forced Photometry From Decam Ugriz and Spitzer/irac Datamentioning
confidence: 99%
“…The riz−band selected DECam catalogs reach a 5σ depth of ∼ 24.5 AB mag. However, we do not use the DE-Cam catalogs and the DECam-selected Spitzer/IRAC forced photometry (Wold et al 2019). In our analysis, we use our new K-band image for detection for the reason we have described in the previous section.…”
Section: Forced Photometry From Decam Ugriz and Spitzer/irac Datamentioning
confidence: 99%
See 2 more Smart Citations